Long haul : hunting the highway serial killers - Figliuzzi, Frank (Mariner Books, 2024)
"From the FBI's former assistant director, a shocking journey to the dark side of America's highways, revealing the FBI Highway Serial Killings Initiative's hunt for the long-haul truckers behind an astonishing 850 murders--and counting"--